Influence of Aggressive Media and Its Effect on Student Behaviour - Azizi Yahaya; Balan Rathakrishnan; Hanum Ahmad; Ismail Maakip; Peter Voo Su Kiong; Mohammad Amin Wani (2020)
This study aimed to find the influence of aggressive media and its effect on student’s behaviour. The study consists 127 students (92 male & 35 female) with problematic discipline from three secondary schools in Kulai District, Johor. The instrument used in the study was a set of questionnaires divided into two parts. Part A is used to look at the background of respondents, whereas section B is used to answer all four research questions. Questionnaire items were measured using a five-step scale. The data obtained were processed using the SPSS 17.0 version to evaluate the percentage of frequency, mean, t-test and correlation test. A pilot study was conducted by the researcher to measure the reliability of the questions in the questionnaire. The findings reported moderate impact of aggressive media on student’s behaviours. Findings for the effects of students' aggressive behaviour are also moderate. This study has important implications on the role of the media in reevaluating broadcast programs in order to minimize aggressive elements that may cause students to act aggressively.